Determinants of dividend policy in small and medium-sized enterprises of an emerging market (2023)
ABSTRACT: This paper aims to analyze the determining factors of dividend policy in SMEs of an emerging economy such as Colombia. SMEs are very important for emerging economies, as they are great job creators and contribute to improving the quality of life of many families. This study is based on liquidity, profitability and indebtedness variables, to demonstrate their links with the dividend policy in this type of entities on which there is not enough empirical research in the Latin American context. A panel data with a total of 11,888 observations was estimated for the horizon 2017-2019. The results evidence that liquidity and profitability increase SMEs’ dividend policy. Indebtedness level indicators present a negative relationship. Overall, the results provide empirical evidence on this important financial decision in a scarcely studied business context and segment. Additionally, the factors influencing dividend policy for these firms have practical implications for regulators, investors, and financial analysts to strengthen their decision criteria in emerging economies.